Bisphenol A and DDT disrupt adipocyte function in the mammary gland: implications for breast cancer risk and progression - Bernhardt, Sarah M.; House, Carrie D. (Frontiers in Oncology, 2025)
As breast cancer incidence continues to rise worldwide, there is a pressing need to understand the environmental factors that contribute to its development. Obesogens, including Bisphenol A (BPA) and Dichlorodiphenyltrichloroethane (DDT), are highly prevalent in the environment, and have been associated with obesity and metabolic dysregulation. BPA and DDT, known to disrupt hormone signaling in breast epithelial cells, also promote adipogenesis, lipogenesis, and adipokine secretion in adipose tissue, directly contributing to the pathogenesis of obesity. While the adipose-rich mammary gland may be particularly vulnerable to environmental obesogens, there is a scarcity of research investigating obesogen-mediated changes in adipocytes that drive oncogenic transformation of breast epithelial cells. Here, we review the preclinical and clinical evidence linking BPA and DDT to impaired mammary gland development and breast cancer risk. We discuss how the obesogen-driven mechanisms that contribute to obesity, including changes in adipogenesis, lipogenesis, and adipokine secretion, could provide a pro-inflammatory, nutrient-rich environment that promotes activation of oncogenic pathways in breast epithelial cells. Understanding the role of obesogens in breast cancer risk and progression is essential for informing public health guidelines aimed at minimizing obesogen exposure, to ultimately reduce breast cancer incidence and improve outcomes for women.